Student Involvement in Science Learning through Direct Instruction Model - Cefi Kurniasih; Ana Andriani (UM Purwokerto Press, 2025)
This study aims to analyze student involvement in learning Natural Sciences (IPA) by implementing the Direct Instruction model. The Direct Instruction model emphasizes the delivery of structured and systematic materials. The Direct Instruction model is used to ensure deep understanding. This study was conducted in grade V using qualitative methods. Data collection techniques used interviews, observations, and document analysis to collect data related to student experiences and interactions during the learning process. The results of the study indicate that the application of the Direct Instruction model can increase student involvement in science learning. Active participation is shown in discussions, exercises, and practical activities in learning. Observations also revealed that students felt more motivated and confident in understanding the science concepts taught. In this study, it was found that the Direct Instruction model is not only effective in delivering materials, but also in increasing student involvement, and can have a positive effect on student learning outcomes.